(untitled) (Asian Education Studies, 2018)
This paper describes a study conducted with twenty-five Japanese lower-level EFL students to develop their ability to write logically in English. In school, Japanese students rarely express their opinions in writing supported by facts or reasons, a result of an important characteristic of Japanese culture: people focus more on emotion than on critical reasoning. Teachers of English often instruct students to add reasons, examples, or conclusions to their written expressions of opinion, but students often fail to do so because they do not grasp their purpose. In this study, students were explicitly instructed in 1) the different values in Western and Japanese culture, 2) alternate ways of thinking and expression, 3) the importance of logic in English rhetoric, and 4) paragraph structure in written English. Students practice writing using English paragraph structure, first in Japanese and then in English. The results indicated that initially only about one third of the students acquired an understanding of how to organize a paragraph logically when writing in Japanese, indicating the difficulty Japanese students have in adopting the principles of English rhetoric even in their native language. After explicit instructions were given repeatedly, another one third of the students were able to structure their paragraphs logically when writing in English. Throughout the six sessions of the study, however, the rest of the students (32%) continued to write their paragraphs in both Japanese and English according to the conventions of Japanese rhetoric, or without logical reasoning.